Evaluation of the risk of inferior alveolar nerve injury during an implant procedure: A comparative study between OPG and CBCT - Hassan A. Barzanji; Alan A. Tahir (Erbil Dental Journal)
Background and objectives: Dental implants are considered as one of the major options for replacement of missing teeth and this surgical procedure may be accompanied by trauma to the adjacent vital structure when there is inadequate information of the implant site. The use of OPG as a preliminary diagnostic instead of CBCT may expose the patient to a high risk of trauma to an inferior alveolar canal. To evaluate the possibility of the risk of endangering inferior alveolar nerve during implant placement using OPG or CBCT as a preoperative assessment tool.